New paleomagnetic pole for the Upper Jurassic Chon Aike Formation of southern Argentina (South America): Testing the tectonic stability of Patagonia with respect to South America, and implications to Middle Jurassic-Early Cretaceous true polar wander - Ruiz González, Víctor (2019)
A paleomagnetic pole and a new Ar-Ar date of 156.08 ± 0.05 Ma are reported for the Chon Aike Formation, an extensive plateau of ignimbrites, outcropping in the Deseado Massif (southern Patagonia, Argentina). The geographic coordinates and statistical parameters for the paleomagnetic pole, validated by a reversal test, are: Lat.=84.3° S, Long.=191.3° E, A95=8.6°, K=13.3, N=23. This pole shows a complete coherence with Late Jurassic and Early to mid-Cretaceous poles of South America, obtained exclusively from igneous rocks, avoiding any potential inclination shallowing. It is suggested that; a) southern Patagonia was an integral part of South America in the Late Jurassic; b) any reported vertical axis tectonic rotations must pre-date the Late Jurassic in this region; c) according to updated paleomagnetic data from igneous rocks, South America had very limited latitudinal drift between about 160 and 140 Ma; and, therefore, d) its apparent polar wander (APW) path, when compared with global apparent polar wander paths, does not support a large global shift or true polar wander (TPW) between 160 and 140 Ma.